Access to hospitals: Potential vs. observed. (May 2020) - Wang, Jiaoe; Du, Fangye; Huang, Jie; Liu, Yu
Abstract: Hospital accessibility is a vital factor in identifying areas with a shortage of healthcare. Due to a lack of data, however, few measures of hospital accessibility in existing studies have considered individual preferences for certain hospitals. To address this issue, we propose the concept of "observed hospital accessibility" (OHA) incorporating trips to the hospital by taxi in Beijing. A comparative analysis was conducted between OHA and the potential hospital accessibility (PHA) method adopted in previous studies. The results suggest that PHA overestimates the accessibility of hospitals in the periphery of the city center where there is more traffic congestion, but underestimates accessibility in the suburbs, as suburban healthcare needs can be met by nearby hospitals. In summary, the OHA method offers a novel approach to employing trip records in the investigation of hospital access behavior when the availability of patient register data is limited. It also provides insights for other activity-based travel behavior studies. Highlights: This study first proposed the concept of observed hospital accessibility (OHA) and conducted an enhanced 2SFCA method with taxi trip data for evaluation. OHA method offers a novel approach to employ trip records for researching out-patient treatment activities. OHA spatially fitted a polycentric structure, whereas potential hospital accessibility (PHA) showed a monocentric structure with the case study of Beijing. The paper provides insights for other activity-based travel behavior study.